Transfusion‐associated circulatory overload in a pediatric intensive care unit: different incidences with different diagnostic criteria. Issue 4 (1st February 2018) - De Cloedt, Lise; Emeriaud, Guillaume; Lefebvre, Émilie; Kleiber, Niina; Robitaille, Nancy; Jarlot, Christine; Lacroix, Jacques; Gauvin, France
Abstract : BACKGROUND: The incidence of transfusion‐associated circulatory overload (TACO) is not well known in children, especially in pediatric intensive care unit (PICU) patients. STUDY DESIGN AND METHODS: All consecutive patients admitted over 1 year to the PICU of CHU Sainte‐Justine were included after they received their first red blood cell transfusion. TACO was diagnosed using the criteria of the International Society of Blood Transfusion, with two different ways of defining abnormal values: 1) using normal pediatric values published in the Nelson Textbook of Pediatrics and 2) by using the patient as its own control and comparing pre‐ and posttransfusion values with either 10 or 20% difference threshold. We monitored for TACO up to 24 hours posttransfusion. RESULTS: A total of 136 patients were included. Using the "normal pediatric values" definition, we diagnosed 63, 88, and 104 patients with TACO at 6, 12, and 24 hours posttransfusion, respectively. Using the "10% threshold" definition we detected 4, 15, and 27 TACO cases in the same periods, respectively; using the "20% threshold" definition, the number of TACO cases was 2, 6, and 17, respectively. Chest radiograph was the most frequent missing item, especially at 6 and 12 hours posttransfusion. Overall, the incidence of TACO varied from 1.5% to 76% depending on the definition. CONCLUSION: A more operational definition of TACO is needed in PICU patients. Using a threshold could be more optimal but more studies are needed to confirm the best threshold.